PENGARUH PEMBERIAN KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN LAPANGAN PT.MULTIGUNA LESTARI ABADI KEMUNING INDRAGIRI HILIR - Siti Ayu Lestari; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The objective of this research wash to find out the effect of compensation and work environment on the performance of field emp;pyes at PT.Multiguna Lestari Abadi Kemuning Indragiri Hilir. This research is located at PT.Multiguna Lestari Abadi Kemuning Indragiri Hilir. The population in this study consisted of 90 employees. Data analysis was carried out by statistical analysis with the help of SPSS. The sampling technique used is the census method and the data technique in this study includes the validity test, reability test, determination test, simple linear regression analysis, multiple linier regression analysis, t-test and F-test and prove the hypothesis. The results showed that and work environment had a significant influence on the performance of fild employees at PT.Multiguna Lestari Abadi Kemuning Indragiri Hilir. Based on the results of the study, the R aquare value of 0.351 means that 35,1% of the Compwnsation and Work Environment variabel affect the performance of field employees at PT.Multiguna Lestari Abadi Kemuning Indragiri Hilir. Keywords: Compensation, Work Environment, employee’s Performance